Specific Features Of Reading And Its Role In Teaching A Foreign Language - Muxabbat Ikromovna Tursunova (Universitas Muhammadiyah Sidoarjo, 2022)
this article deals with the identifying the most effective methods and means of teaching reading in foreign language lessons. In addition, author provides the techniques and means of teaching reading and identifies those that contribute to the formation of interest in reading in a foreign language.